Industrial strategies and policies in Malaysia since 1959: A case study of manufacturing sector / Noraini Ibrahim - Noraini, Ibrahim (1984)
The major industrial policies in malaysia are tariffs, fiscal incentives and industrial estates. The two main pillars on which malaysia industrial strategy is based are tariffs and fiscal incentives. These two instruments have been used to stimulate the growth of manufacturing sector, even though there has been considerable controversy in regard to their effectiveness. Nevertheless, tariffs and fiscal incentives were equally used in malaysian industrial strategy in order to hasten the development of manufacturing activity. Another major problem in the development of industrial activities in malaysia was the consentration of activity in a few developed states. One of the difficult tasks of industrial planning is to direct industrial activity into less developed states thus aiming to redress uneven regional development. To achieve this aim, industrial estates were used as an instrument of regional development. This chapter, assesses some of the impact of these major industrial policies, perticularly fiscal incentives, tariff protection and industrial estates.